Analyzing bottlenecks for institutional development in Central Asia: Is it oil, aid, or geography? - Inna Melnykovska; Rainer Schweickert (PFH Private Fachochschule Göttingen, 2009)
The quality of institutions is considerable worse in Central Asia than in other transition countries. Based on a panel of 25 transition countries for the period from 1996 to 2005, this paper shows that oil and aid exert a negative influence on institutional development. At the same time, transition countries benefited from external incentives due to cultural proximity to the West or a membership perspective in either EU or NATO. However, the evaluation for Central Asia reveals that aid, oil, and geography explain part of the backlog but, even accounting for the fact that the countries are "far away" and do not benefit from external incentives as do other transition countries, there is a strong and homogenous negative regional component of bad governance. Hence, change might come but at a very low pace.
Keywords: F15; F20; F50; P20; P30; O19; 330; EU; NATO; Transition Economies; Institutional Change; Governance; Central Asia; Institutioneller Wandel; Übergangswirtschaft; Good Governance; Internationale Wirtschaftshilfe; Mineralölwirtschaft; Geopolitik; Zentralasien